Il fattore "tempo" nella giustizia costituzionale - FIANO, NANNEREL (Politica, diritto, 2022)
The volume investigates the management of the "time" factor in the context of constitutional justice from the point of view of the modulation of the effects over time of the declaration of unconstitutionality and the technique of referral to the legislature. The analysis is intertwined with the study of the German experience of incompatibility decisions, which allow the German Federal Constitutional Court to declare only the incompatibility of a rule and, at the same time, to order the legislature to intervene to remove the constitutional defect. An in-depth study of this type of decision allows us to highlight some important aspects on the governance of the effects of the declaration of unconstitutionality and on the decision-making technique of unconstitutionality envisaged in Italian constitutional justice.